2017
DOI: 10.3389/fpsyg.2017.01341
|View full text |Cite
|
Sign up to set email alerts
|

The Dark Side of Malleability: Incremental Theory Promotes Immoral Behaviors

Abstract: Implicit theories drastically affect an individual’s processing of social information, decision making, and action. The present research focuses on whether individuals who hold the implicit belief that people’s moral character is fixed (entity theorists) and individuals who hold the implicit belief that people’s moral character is malleable (incremental theorists) make different choices when facing a moral decision. Incremental theorists are less likely to make the fundamental attribution error (FAE), rarely m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 55 publications
(73 reference statements)
0
12
0
Order By: Relevance
“…Research has consistently demonstrated that people hold differing beliefs about the fixed or mutable nature of a variety of self-attributes such as intelligence (Blackwell et al, 2007;Dweck et al, 1995;Robins and Pals, 2002), personality (Erdley et al, 1997;Chiu et al, 1997b), morality (Chiu et al, 1997a;Huang et al, 2017), emotions (King and dela Rosa, 2019;Tamir et al, 2007;De Castella et al, 2013), and relationships (Knee, 1998;Knee et al, 2003;Ng and Tong, 2013), among others. These types of beliefs are referred to as implicit self-theories (Dweck and Leggett, 1988;Molden and Dweck, 2006) -or, more colloquially, mindsets.…”
Section: Implicit Self-theoriesmentioning
confidence: 99%
“…Research has consistently demonstrated that people hold differing beliefs about the fixed or mutable nature of a variety of self-attributes such as intelligence (Blackwell et al, 2007;Dweck et al, 1995;Robins and Pals, 2002), personality (Erdley et al, 1997;Chiu et al, 1997b), morality (Chiu et al, 1997a;Huang et al, 2017), emotions (King and dela Rosa, 2019;Tamir et al, 2007;De Castella et al, 2013), and relationships (Knee, 1998;Knee et al, 2003;Ng and Tong, 2013), among others. These types of beliefs are referred to as implicit self-theories (Dweck and Leggett, 1988;Molden and Dweck, 2006) -or, more colloquially, mindsets.…”
Section: Implicit Self-theoriesmentioning
confidence: 99%
“…Li & Bates, 2019;see Mueller & Dweck, 1998;, there is robust evidence to support the e ectiveness of manipulating mindsets about malleability in the wider population (Andersen & Nielsen, 2016). Of particular relevance to the current study are ndings indicating that one's mindset of malleability can be e ectively primed by reading a short article with persuasive empirical evidence in support of the notion that change is possible in various domains, such as intelligence (Bergen, 1991;Hong et al, 1999;Nussbaum & Dweck, 2008), body weight (Burnette, 2010), personality and character (Chiu et al, 1997;Rattan & Dweck, 2010), criminal behavior (Rade et al, 2018), and morality (Huang et al, 2017).…”
Section: Mindsets About Malleabilitymentioning
confidence: 67%
“…A xed mindset concerning personality traits predicts aggressive desires and produces more hostile attributional biases (Yeager et al, 2013). By contrast, a malleable mindset is related to a greater tolerance of immorality (Huang et al, 2017), a greater willingness to forgive (Iwai & de França Carvalho, 2020), more compassionate legal assessments (Weimann-Saks et al, 2019), and decreased support for harsh sanctions (Plaks et al, 2009). Consequently, relative to those with a xed mindset, people with a malleable mindset are less likely to assert attributions of internal proclivity for criminal behavior and to expect o enders to re-o end, and they are more likely to make less punitive judgments (Tam et al, 2013).…”
Section: Mindsets About Malleabilitymentioning
confidence: 99%
“…In general, there is some disagreement on whether an individual's character, competence and attitude is rather fixed (entity theory) or malleable (incremental theory) [21]. The importance of a theorist's respective viewpoint on the assessment of actual behavior was confirmed in previous research [22].…”
Section: Theoretical Backgroundmentioning
confidence: 99%